Biofuels and Bioenergy: Biofuels and Bioenergy, edited by Jhon Love and John A. Bryant, John Wiley & Sons, 2017, 299 pp., €86.9, Print ISBN: 9781118350560; Online ISBN: 9781118350553. Issue 1 (31st December 2022) - Gunasekar, P.; Manigandan, S.
Abstract : The global demand for energy is increased owing to the growth of automobile sectors and population. From decades, the fossil fuels act as the primary source of energy in the market. Exhausting of fossil fuels and increasing of emission made the pioneers to switch to clean and green renewable energy. Recently, several inventions found that biodiesel is a suitable alternative to replace oil. However, the emission of NOx is a worry and lately it is found by employing nanoparticles in the fuel NOx can be dropped. In this book review, an attempt has been made to see the sights of the biodiesel production and its usage in an ethical way. This book delivers the board classification in the production of biofuels using various sources such as waste, food and algae. The authors of the book made excellent effort to cover the production of fuel in the aspect of ecology and land use.